On Noetherian Modules over Minimax Abelian Groups - Tushev, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider modules over minimax Abelian groups. We prove that if A is an Abelian minimax subgroup of the multiplicative group of a field k and if the subring K of the field k generated by the subgroup A is Noetherian, then the subgroup A is the direct product of a periodic group and a finitely generated group.